Interannual variability and evolution during the montanera period of Holm oak (Quercus rotundifolia Lam.) acorns - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Cava, R.; Vázquez, F. M. (Spanish Journal of Agricultural Research, 2010)
Eighty-eight samples of Quercus rotundifolia acorns were analyzed during three consecutive years (2005/06, 2006/07 and 2007/08) to determine variations in their morphology, sanitary condition, and nutritional composition throughout the same period of montanera (free-range swine-raising system of SW Iberia) and between different years of study. Results showed that morphological characteristics remained constant throughout montanera season. Fungal damage increased, and Curculio sp. and Cydia sp. pests decreased over the course of the montanera season. Dry matter content decreased in both kernel and pericarp (P < 0.001), while the crude fiber and protein contents were not modified. The ash, nitrogen-free extract, and fat contents, however, were also affected by sampling date within a montanera season. With respect to the interannual variability, variations (P < 0.05) were observed in all the variables studied. It is therefore confirmed that there is variability in the sanitary condition and nutritional composition of acorns within the same montanera season and between different years of study. These could explain the differences in the chemical characteristics of Iberian pig tissues from animals raised in different montanera seasons, and even during the same montanera season.
Keywords: acorn sanitary condition; Dehesa; feeding; Iberian pigs; proximate composition

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F.; Vázquez, F. M.; Burzaco, A.; Perez, M. C. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus